KONTROVERSI IDDAH PEREMPUAN MENGGUGAT CERAI - Abdurrasyid Ridha (Balai Diklat Keagamaan Bandung, 2022)
This research was motivated by the controversy over Hambali’s that iddah for women is one menstrual period. Meanwhile, according to the major sects, the iddah is three times of quru', and based on Indonesian marriage regulations, the iddah is 90 days. Hambali’s view of thought is based on certain traditions. So this study aims to determine the validity of these traditions. This research is a takhrijul hadith’s study using descriptive method in form of content analysis. An important finding was found that it turns out that the traditions used as the legal basis for one-time menstrual iddah are da'if. The finding is something new because some scholars think that the traditions are valid. This finding is important for the public, so that it is not easy to accept the sect’s opinions that are widely spreaded on the internet. For the marriage officiants, this finding is also important in order to have more confidence towards existing regulations.Keywords: khulu’; iddah; divorce; takhrij